Åloppe Faunal Remains - Gummesson, Sara (Stockholm University, 2024)
Database of zooarchaeological analyzes of material from the Neolithic site Åloppe, Norrskog, Uppland, Sweden.
For specified information about the content and analysis, please consult the Description of sampling (in the Collection and method section further down) and the README-file in the Documentation.

Databas över animalosteologiska analyser av material från den neolitiska lokalen Åloppe, Norrskog, Uppland, Sverige.
För mer specifik information om innehåll och analys, se Beskrivning av urval (i avsnittet Insamling och metod) och README-filen i Dokumentation.
Åloppe faunarester
Keywords: osteology; osteologi; Alces (genus); Sus (genus); osteology; Mammalia (class); Phocidae (family); Ungulata (former order); Zoology; Zoologi; Archaeology; Arkeologi; Scientific analysis; Scientific analysis